Understanding human immunity in idiopathic recurrent pregnancy loss. (March 2022) - Bagkou Dimakou, Danai; Lissauer, David; Tamblyn, Jennifer; Coomarasamy, Arri; Richter, Alex
Abstract: Miscarriage, defined as the loss of a pregnancy before a viable gestation, affects 1 in 6 couples. Recurrent pregnancy loss (RPL), defined as two or more miscarriages, affects up to 1.9% of couples. The physical, psychological, and financial impact of miscarriage can be substantial. However, despite its multifactorial etiology, for up to 50% of couples a reason behind this condition cannot be identified, termed 'idiopathic RPL'. Much recent research has strived to understand this, with immune dysregulation being a source of particular interest. In this short review we summarize the current evidence on the complex role of the immune system both pre- and early post-conception in RPL. A key question is whether systemic peripheral blood markers, in particular natural killer cell and T cells, may be utilized to accurately predict and/ or diagnose those pregnancies at high risk of loss. Given the invasive nature of endometrial testing, identification of reliable peripheral immune biomarkers is particularly appealing. Clinical trials using potent immunomodulatory agents, including intravenous immunoglobulin, donor leukocyte immunization, and tumor necrosis factor (TNF)-α inhibitors, have been undertaken with the primary objective of preventing miscarriage in women with RPL. Standardisation of both diagnostic and prognostic immune cell testing assays is required to permit accurate identification of those women who may benefit from immunomodulation. Prompt clarification is required to meet the increasing expectation from couples and clinicians, as without these advancements women are at risk of exposure to potent immune-therapies and subsequent studies are at risk of failure, generating further controversy regarding the role of immune dysregulation in women with RPL. Through this review we highlight clear gaps in our current knowledge on immune activity in RPL.